Quantitative wood anatomy of Juniperus excelsa from Lebanon as a potential hydroclimate archive - Mdawar, Mansour; Balanzategui, Daniel; Touchan, Ramzi; Ziaco, Emanuele; Dorado-Liñán, Isabel; Helle, Gerhard; Heinrich, Ingo (Frontiers in Plant Science, 2025)
The Middle East and North Africa is a hotspot for negative climate change impacts and potentially for conflicts over water resources. To protect future generations from destabilization and marginalization, governments need to consider the impact of climate change on water management issues. Long-term hydroclimatic information is needed for a reliable management of the water resources. However, only a few continuous high-quality meteorological records exist in MENA starting in the early 1900s, while the majority of existing records cover just the second half of the twentieth century, hence alternative sources such as tree-ring proxies to describe past climate dynamics will be a valuable add-on. Tree-ring width records of Greek juniper (Juniperus excelsa M. Bieb) have already been demonstrated to be useful for extending existing instrumental climate records. For the first time, we investigated the dendroclimatological potential of J. excelsa growing in the Lebanese mountains, focusing, also for the first time, on quantitative wood anatomy. We measured cell lumen diameter in radial direction and cell wall thickness in tangential direction for the tree rings formed during the years 1963 to 2019. The measurements were then correlated with monthly and seasonal climate records. Strongest correlations were found between lumen diameter and current May precipitation (positive) as well as maximum temperature (negative). Lumen diameter also exhibited significant correlations with drought during May and July to September). Climate correlations with tree-ring width were generally less significant. The study showed, for the first time, declining trends in the cell lumen and cell wall data since the early 1990s suggesting that in the Lebanese Mountains this important tree species J. excelsa seems to have been under increasing drought stress. The preliminary findings highlight the feasibility of building long chronologies of quantitative wood anatomical parameters for J. excelsa from the Lebanese mountains and the potential of such measurements as a paleoclimate archive, especially when focusing on water availability and drought patterns.